2015
DOI: 10.1016/j.cardfail.2015.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Use of Post-acute Care Services and Readmissions After Left Ventricular Assist Device Implantation in Privately Insured Patients

Abstract: Background Very little is known about healthcare resource utilization, including post-acute care use and hospital readmissions, following left ventricular assist device (LVAD) implantation. Methods and Results Administrative claims from a database of multiple U.S. health plans were used to identify patients that received an LVAD (ICD-9 code 37.66) and survived to hospital discharge from January 1, 2006 through September 30, 2013. Post-acute care use was defined as a skilled nursing facility or rehabilitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…10,12 Bed size, teaching, and geographic location (urban versus rural) were included to adjust for hospital variability in OHT and VAD performance. 5,13 Hierarchic regression adjusting for hospital covariance in the nested sampling design was utilized as recommended for the NRD database. Mortality, duration of stay, and log-transformed costs were modeled using logistic, Poisson, and linear distributions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…10,12 Bed size, teaching, and geographic location (urban versus rural) were included to adjust for hospital variability in OHT and VAD performance. 5,13 Hierarchic regression adjusting for hospital covariance in the nested sampling design was utilized as recommended for the NRD database. Mortality, duration of stay, and log-transformed costs were modeled using logistic, Poisson, and linear distributions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, readmissions at other institutions were not captured in this study. However, recent data suggests that 86% of readmissions after LVAD are to the implanting hospital 22 . In addition to the limitations, there are several notable strengths.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a retrospective analysis of administrative claims data from a large US commercial insurance database, Optum Labs Data Warehouse, which is comprised of privately insured enrollees from geographically diverse regions across the country. 10,11 The database includes professional, facility, and outpatient medication service claims for individuals enrolled in private and Medicare Advantage health plans. 12 Because this study involved analysis of preexisting, de-identified data, it was exempt from institutional review board approval.…”
Section: Methodsmentioning
confidence: 99%